The Effectiveness of Acceptance and Commitment Therapy on Depression and Cognitive Biases in Married Women - Molaie, Rouhangiz (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to evaluate the effectiveness of Acceptance and Commitment Therapy (ACT) on reducing depression and cognitive biases in married women. Methods and Materials: A randomized controlled trial was conducted with 30 married women in Tehran who exhibited elevated depressive symptoms and cognitive biases. Participants were randomly assigned to an experimental group (n = 15) receiving eight weekly 75-minute ACT sessions or a control group (n = 15) receiving no psychological intervention. Depression and cognitive biases were assessed at pretest, posttest, and five-month follow-up using the Beck Depression Inventory-II and the Cognitive Bias Questionnaire. Data were analyzed using repeated measures ANOVA with Bonferroni post-hoc tests in SPSS-27. Findings: Repeated measures ANOVA indicated significant time × group interactions for depression (F(2, 54) = 45.22, p < .001, η² = .63) and cognitive biases (F(2, 54) = 39.52, p < .001, η² = .60). Bonferroni tests showed significant reductions in depression and cognitive bias scores from pretest to posttest (p < .001) and pretest to follow-up (p < .001) in the experimental group. No significant differences were found between posttest and follow-up scores (p > .05), indicating stability of treatment effects. Conclusion: Findings suggest that Acceptance and Commitment Therapy is effective in reducing depressive symptoms and cognitive biases in married women and that these benefits persist over a five-month follow-up. ACT may offer a promising therapeutic option for addressing both emotional and cognitive vulnerabilities in this population by promoting psychological flexibility and values-based action.